An Overview of Consultant Nursing Specialist in Clinical Practice (2011)
As most health care systems around the world are undergoing major restructuring, nurses in Nigeria are moving at a slow pace. However, a giant stride was taken and history was made when the first set of nurse consultants were appointed in University College Hospital, Nigeria. The establishment of this groundbreaking post will help develop our health services and provide clear development opportunities for nurses at a time when the success of modernization of our services and implementation of new ways of working relies so heavily on nursing staff. This paper provides an overview of the consultant nurse specialist in clinical practice. Recommendations for successful implementation in Nigeria were provided.